2016
DOI: 10.1016/j.bbr.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Possible contribution of epigenetic changes in the development of schizophrenia-like behavior in vasopressin-deficient Brattleboro rats

Abstract: Schizophrenia-like symptoms were detected in vasopressin-deficient (di/di) Brattleboro rats, and it was also suggested that schizophrenia might have an epigenetic component. We aimed to clarify if epigenetic changes contribute to schizophrenia-like behavior of this strain. Behavioral (locomotion by telemetry, cognition by novel object recognition, social recognition and social avoidance test, attention by pre-pulse inhibition) and epigenetic differences were compared between wild type and di/di animals. DNA me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 99 publications
1
16
0
Order By: Relevance
“…Third, it is plausible that chronic exposure to dDAVP and second messengers such as cAMP are required for detectable changes in K-acetylation. For example, Brattleboro rats, which lack endogenous vasopressin, have reduced K-acetylation of histone H3 K9 in different regions of the brain compared with control rats (15). Moreover, chronic 16 and 48 h of vasopressin to L6 myogenic cells significantly increased K-acetylation (59).…”
Section: Discussionmentioning
confidence: 99%
“…Third, it is plausible that chronic exposure to dDAVP and second messengers such as cAMP are required for detectable changes in K-acetylation. For example, Brattleboro rats, which lack endogenous vasopressin, have reduced K-acetylation of histone H3 K9 in different regions of the brain compared with control rats (15). Moreover, chronic 16 and 48 h of vasopressin to L6 myogenic cells significantly increased K-acetylation (59).…”
Section: Discussionmentioning
confidence: 99%
“…Our research group demonstrated the possible role of histone modification in the development of schizophrenia-like behavior in genetically AVP deficient Brattleboro rat (without changes in the enzymes responsible for DNA methylation, DNA methyltransferase, DNMT1 and DNMT3a) [16]. In AVP deficient animals, Western-blot measurements showed lower pan-AcH3 (histone 3 acetylation) immunoreactivity in the frontal part of the brain with elevated levels in the hippocampus.…”
Section: Histone Modifications and Vasopressinmentioning
confidence: 83%
“…AVP determines behavioral responses to environmental stimuli and participates in the development of social interactions, aggression, reproduction, parental behavior and belonging [4,10,11]. Therefore, alterations in the AVPergic tone may be implicated in the pathology of stress-related disorders (anxiety and depression) [12], Alzheimer's disorder [13], posttraumatic stress disorder [14] as well as schizophrenia [15][16][17].…”
Section: Vasopressin and Stressmentioning
confidence: 99%
“…Interestingly, the study by Bhardwaj, Stojkovic, Kiessling, Srivastava, and Cermakian (2015) has found that constant lighting exerts unremitting effects on the behavior of Dtnbp1 mutant mice, leading to PPI and anxiety‐like behaviors while reintroducing the mice into the normal light–dark cycle fails to completely reverse the disordered behaviors. Lately, Demeter et al (2016) has proposed that the Brattleboro rat strain lacking arginine vasopressin (AVP) is a valuable model for studying the development of schizophrenia‐like behavior and investigating the expression of affected genes. Animal experimental models provide convenience when examining changes in genetic status and testing newly discovered antipsychotics.…”
Section: Animal Experimental Model Of Genetic‐environmental Interactionmentioning
confidence: 99%